Modern Normative and Technical Support of Complex Technical Systems Projects - Світлана Кривова; Олександр Зубаньов; Костянтин Зворикін; Сергій Трубачев (Mechanics and Advanced Technologies, 2022)
It is considered relevant to assess the potential of modern normative and technical support for programs/ life cycle projects of complex technical systems, which is based on system, process and project approaches, as well as on risk-oriented thinking, which is an integral condition for achieving (maintaining) competitiveness not only of products produced by the organization, but also the competitiveness of the organization itself.